Urinary Catheter Colonization by Multidrug-Resistant Cedecea neteri in Patient with Benign Prostatic Hyperplasia - Peter S. Ginn; Serina B. Tart; Stephen M. Sharkady; Dorothea K. Thompson (Case Reports in Infectious Diseases)
Cedecea neteri, a member of the Enterobacteriaceae family, has only been identified as a human pathogen in a few previous clinical cases, thus complicating assessment of this organism’s pathogenicity and medical relevance. Documented infections attributed to C. neteri primarily involved bacteremia in severely immunocompromised patients. We report a rare case of urinary catheter colonization by a multidrug-resistant C. neteri strain in a patient of advanced age with benign prostatic hyperplasia and other chronic comorbidities. This C. neteri isolate was resistant or intermediate to second-generation cephalosporins, penicillins, and certain β-lactamase inhibitor/β-lactam combinations. Analysis of whole genome sequence information for a representative C. neteri strain indicated the presence of multiple open reading frames with sequence similarity to β-lactamases, including a chromosome-encoded AmpC β-lactamase and metallo-β-lactamases, consistent with the resistance phenotype of this bacterium. The presence of an AmpR homolog suggests that the C. neteriampC may be inducible in response to β-lactam exposure. Molecular insights into antibiotic resistance traits of this emerging opportunistic pathogen will be important for administering adequate antibiotic treatment to ensure favorable patient outcomes.